Odd Child Out : Cranberry Cove #2 - Macmillan, Gilly (New York, NY : William Morrow, 2017)
Investigating the death of a man who may have been a casualty of a prank gone wrong, detective Jim Clemo is embroiled in a public debate surrounding the victim and his best friend, a Somali refugee who is unwilling or unable to reveal what happened.
Investigating the death of a man who may have been a casualty of a prank gone wrong, detective Jim Clemo is embroiled in a public debate surrounding the victim and his best friend, a Somali refugee who is unwilling or unable to reveal what happened.
Keywords: Secrecy -- Fiction; Family life -- Fiction; Secrets -- Fiction; Family problems -- Fiction; Suspense fiction